Racism without race: The racialization of Muslim Middle Eastern and North African international students at U.S. college - Mesouani, Hannah (Journal of International Students, 2025)
By utilizing foundational texts on critical race theory, scholarships on Muslim Americans, and the Ethnic Identity Scale (EIS), this mixed methods study examines Muslim Middle Eastern and North African (MENA) racial identity development amid America’s tense history with Islam and the MENA world. The findings revealed that participants were 53% more likely to identify as Black within the U.S. census schema, and when self-identifying, 42% of participants chose new identity terminology such as Arab or Middle Eastern. The participants felt most comfortable with other Muslim international students and Black and Muslim U.S. peers and reported self-isolation from white spaces. The participants who identified as MENA experienced more pride in their heritage than those who identified as white. These findings illuminate the need for increased MENA and Muslim representation and offer recommendations at the governmental, educational, and individual levels to combat the weaponization of whiteness that downplays the dangers of Islamophobia.